Microgrid Policies: A Review of Technologies and Key Drivers of Thailand - Meenual, Thongchai; Usapein, Parnuwat (Frontiers in Energy Research, 2021)
A microgrid has been emerging and playing its valuable roles in several parts of society, from academia of scholars to the energy supply industry of professional practitioners. Because of its beneficial renewable energy promotion, the microgrid is in various locations of lab-scale demonstration sites as well as rural and urban communities at the local, national, and future international levels. A microgrid policy appears in a Thailand 2015 energy development plan. There are many microgrid projects in Thailand. One installed demonstration microgrid project is in active operation; another larger microgrid project is under installation, and; the remaining microgrid projects are in the process of conceptual design and procurement. The objective of this research is to investigate the compatible microgrid technology in Thailand and explore the key drivers of microgrid policies in Thailand. The research methodology applied in this research includes data collection (i.e., a document study, interview, group discussion, and microgrid project participation and observation), as well as data analysis and conclusion. The findings of the research show that: in Thailand, the desired microgrid technologies are compatible with (i) inputs of potential local renewable energy resources of solar, wind, biomass, and mini-hydro, and (ii) small gaps of human resource capabilities to deal with the technology utilization; and the key drivers of Thailand microgrid policy are (i) electricity access, (ii) wealth creation and distribution, (iii) environmental protection, and (iv) technology development.